An unsaturated amido-substituted six-vertex germanium cluster and its reactions with alkenes and alkynes. Issue 34 (21st July 2020) - Helmer, Joschua; Hepp, Alexander; Lips, Felicitas
Abstract : Starting from the germylene {N(SiMe3 )Dipp}GeCl·DMAP 1 the unsaturated germanium cluster Ge6 {N(SiMe3 )Dipp}4 2 was obtained. This cluster reacts as a masked digermyne in cycloadditions with ethylene, diphenylacetylene and 2, 3-dimethyl-1, 3-butadiene. Abstract : The unsaturated metalloid germanium cluster Ge6 {N(SiMe3 )Dipp}4 2 with two ligand-free germanium atoms and only four amine substituents was obtained starting from the base-coordinated germylene {N(SiMe3 )Dipp}GeCl·DMAP 1 in 50% yield (DMAP = 4-(dimethylamino)-pyridine). This cluster reacts as a masked digermyne in cycloadditions with ethylene, diphenylacetylene and 2, 3-dimethyl-1, 3-butadiene in toluene at 100 °C to yield 3–5 .